2020
DOI: 10.3390/s20020360
|View full text |Cite
|
Sign up to set email alerts
|

Smart Build-Plate for Metal Additive Manufacturing Processes

Abstract: This paper discusses the development, processing steps, and evaluation of a smart build-plate or baseplate tool for metal additive manufacturing technologies. This tool uses an embedded high-definition fiber optic sensing fiber to measure strain states from temperature and residual stress within the build-plate for monitoring purposes. Monitoring entails quality tracking for consistency along with identifying defect formation and growth, i.e., delamination or crack events near the build-plate surface. An alumi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 21 publications
0
13
0
Order By: Relevance
“…In Dunbar et al (2016), a displacement sensor was attached to the underside of the baseplate. A more recent study (Hehr et al 2020) presented a smart baseplate for L-PBF with an embedded optical fibre strain measurement sensor.…”
Section: Level 4 Methodsunder the Layermentioning
confidence: 99%
See 1 more Smart Citation
“…In Dunbar et al (2016), a displacement sensor was attached to the underside of the baseplate. A more recent study (Hehr et al 2020) presented a smart baseplate for L-PBF with an embedded optical fibre strain measurement sensor.…”
Section: Level 4 Methodsunder the Layermentioning
confidence: 99%
“…Rather than measuring the baseplate deformation, Hehr et al (2020) demonstrated the feasibility of the proposed approach to detect plastic deformations like a delamination from the baseplate.…”
Section: Level 4 Methodsunder the Layermentioning
confidence: 99%
“…Over the last few years and based on techniques of incorporation of FOSs, a set of systems has been developed that allows the monitoring of strains, temperature variations and cracking, using mainly FOSs of FBG type [76][77][78][79][80][81][82][83][84][85]. Xiao Chun Li et al [76][77][78][79] is one of the main boosters in the development of methodologies capable of integrating sensors into metal components, using in this case, low-temperature processes, magnetron sputtering and electroplating.…”
Section: Applications For Metal Componentsmentioning
confidence: 99%
“…Schomer et al [81], Chilelli et al [84] and Hehr et al [85] demonstrated the feasibility of integrating FOSs into metal matrices through UAM and monitoring temperature, cracks and residual stress, respectively, into structural components. This type of process also has great potential to monitor components present in environments subject to high temperatures, which does not happen with piezoelectric sensors as further forward will be analysed.…”
Section: Applications For Metal Componentsmentioning
confidence: 99%
See 1 more Smart Citation